Experimental study on condition assessment of reinforced concrete structure using a dynamics response approach. Issue 2 (2014) - Chun Pong Sing; P.E.D. Love; P.R. Davis
<x xml:space="preserve"> Abstract </x> Purpose – Condition assessment on reinforced concrete (RC) structures is one of the critical issues as a result of structure degradation due to aging in many developed countries. The purpose of this paper is to examine the sensitivity and reliability of the conventional dynamic response approaches, which are currently applied in the RC structures. The key indicators include: natural frequency and damping ratio. To deal with the non‐linear characteristics of RC, the concept of random decrement is applied to analyze time domain data and a non‐linear damping curve could be constructed to reflect the condition of RC structure. Design/methodology/approach – A full‐scale RC structure was tested under ambient vibration and the impact from a rubber hammer. Time history data were collected to analyze dynamics parameters such as natural frequency and damping ratio. Findings – The research demonstrated that the measured natural frequency is not a good indicator for integrity assessment. Similarly, it was revealed that the traditional theory of viscous damping performed poorly for the RC with non‐linear characteristics. To address this problem, a non‐linear curve is constructed using random decrement and it can be used to retrieve the condition of the RC structure in a scientific manner. Originality/value – The time domain analysis using random decrement can be used to construct a non‐linear damping curve. The results from this study revealed that the damage of structure can be reflected from the changes in the damping curves. The non‐linear damping curve is a powerful tool for assessing the health condition of RC structures in terms of sensitivity and reliability.